The Study of Risk Factors and Management of Obesity in Children : A Comprehensive Systematic Review - Patrick Luckend Sahusilawane; Oktavia Henny (The International Journal of Medical Science and Health Research, 2025)
Background: Childhood obesity is a significant global public health issue, with a significant association between risk factors and management. Factors such as reduced physical activity and increased access to processed foods contribute to this trend. Management is crucial to prevent obesity-related health issues in adulthood, as obesity can lead to complications like type 2 diabetes, dyslipidemia, and cardiovascular diseases. Early intervention and lifestyle modifications can reduce the risk of obesity-related comorbidities, but the feasibility of implementing intensive programs may be challenging. Methods: This systematic review focused on full-text English literature published between 2014 and 2024, adhering to PRISMA 2020 principles. Without a DOI, editorials and review papers that were published in the same journal as the submission were not accepted. ScienceDirect, PubMed, and SagePub were among the many web resources used to compile the literature. Result: Utilizing dependable sources such as Science Direct, SagePub, and PubMed, the investigation scrutinized nearly 100,000 articles. After determining that ten publications required additional investigation, a more comprehensive review of the entire corpus was carried out. Conclusion: Pediatric obesity is a complex issue influenced by behavioral, genetic, socioeconomic, and environmental factors. Environmental factors, such as high-calorie foods and fast-food, disrupt prefrontal executive-control responses. Genetic similarities between obese adults and children have been discovered. Treatment options include nutrition, exercise, psychological therapy, pharmacotherapy, and surgical procedures. However, treatment outcomes can vary widely, necessitating a comprehensive baseline assessment.